Peran Koping Religius dan Kesejahteraan Subjektif Terhadap Stres pada Anggota Bintara Polisi di Polres Kebumen - Amalia Juniarly (Fakultas Psikologi dan Ilmu Sosial Budaya Universitas Islam Indonesia Yogyakarta, 2012)
This study aims to determine the role of religious coping and subjective well-being to stress on the non-commissioned members of the police at the police resort Kebumen. Research subjects were the non-commissioned members of the Sabhara police force at police resort Kebumen and muslims. Data collection methods used scale. The results were analyzed using partial correlation analysis. Coefficient correlation between stress and religious coping of - 0.517 with p = 0.000 (p <0.01), while the coefficient of correlation with subjective well-being of - 0.309 with p = 0.022 (p> 0.01). This suggests that there was a significant negative correlation between religious coping, subjective well-being and stress. The higher religious coping and subjective well-being levels, the lower the stress levels. In other words, stress can be predicted based on religious coping and subjective well-being. Thus, the hypothesis accepted.Keywords: Religious Coping, Subjective Well-Being, Stress